Viabilidade econômica da produção de milho e soja influenciada por doses de calcário e gesso - Vinicius Mosca Aguero (2021)
ABSTRACT The use of limestone and agricultural gypsum can promote changes in the costs of a production that can alter its productivity. In this way, the objective was to evaluate the economic viability of the production of soybeans and corn occurred in different doses of limestone with and without combination of surface gypsum. The experiment was conducted in the experimental area of the Universidade Federal de Mato Grosso do Sul at Chapadão do Sul, in a dystrophic Red Latosol, a clayey texture. The design was arranged in randomized blocks in factorial 5 (doses of limestone) x 2 (absence and presence of gypsum) with four replications. Grain yield in corn and soybean was evaluated. Costs were organized following the Effective Operating Cost (COE) and Total Cost (TC) structure. To determine the viability of crops, tables were drawn up and economic indicators were applied: Gross Revenue, Operating Profit, Leveling Point, Equilibrium Price and Profitability Index..The total cost of crops was R$ 2,939.27 and R$ 2,242.85 for soybean and corn, respectively. The cultivation of soybean and corn were economically viable activities for the study region, with the treatment with application of 800 kg ha-1 of limestone, without the presence of gypsum, which showed greater viability for both soybean and for the corn.